Kāvyakirīṭa Śrīmanta Pratapasĩha Mahārāja Gāyakavāḍa yāñcyā rājyabhishekācẽ kāvya - Yaśavanta, 1899-1985 (SAMP early 20th-century Indian books project, 1900)
Narrative poem describing coronation of Pratāpasiṃha Gāyakavāḍa, Maharaja of Baroda.